Financial Literacy and Green Finance Adoption among Working Professionals in Nepal - Kandel, Madan; Bhattrai, Dhundi Raj; Shakya, Rosma (Nepal Journal of Multidisciplinary Research, 2025)
Background: Green finance is more than just a slogan—it’s a pathway toward a cleaner, more sustainable future. Yet in Nepal, its adoption remains slow so, professionals still face barriers like lack of knowledge, poor access to eco-friendly financial products, low environmental awareness, and lack of supportive government policies Objectives: The major aim of this research is exploring key influences: financial literacy, environmental awareness, government incentives, and access to green financial products to uncover how each of these factors affects green finance adoption. Methods: The study gathered information from working individuals through a five-point Likert scale questionnaire. The research design blended descriptive, correlational, and causal-comparative approaches. Findings: Financial literacy, environmental awareness, government incentives, and product access had a positive impact on green finance adoption but financial literacy raised out. People who had a good understanding of how money and investments work were much more likely to choose options that help protect the environment. Conclusion: If Nepal wants to accelerate its journey toward sustainable finance, it must start by educating its people. Together with better access to green financial products and smarter government incentives, financial education can empower professionals to invest with both their wallets and their values. Novelty: It’s not just theory it’s a practical roadmap and fresh localized evidence-based aspect which drives green finance behavior in Nepal. By investing in financial education and product accessibility, they concern can build a culture of sustainable investment that benefits individuals and research communities.